Social structural factors that shape assisted injecting practices among injection drug users in Vancouver, Canada: a qualitative study - Fairbairn Nadia; Small Will; Van Borek Natasha; Wood Evan; Kerr Thomas (BMC, 2010)
Abstract Background Injection drug users (IDU) commonly seek manual assistance with illicit drug injections, a practice known to be associated with various health-related harms. We investigated the social structural factors that shape risks related to assisted injection and the harms that may result. Methods Twenty semi-structured qualitative interviews were conducted with IDU enrolled in the ACCESS or Vancouver Injection Drug Users Study (VIDUS) who reported requiring assistance injecting in the past six months. Audio-recorded interviews were transcribed verbatim and a thematic analysis was conducted. Results Barriers to self-injecting included a lack of knowledge of proper injecting technique, a loss of accessible veins, and drug withdrawal. The exchange of money or drugs for assistance with injecting was common. Harms experienced by IDU requiring assistance injecting included theft of the drug, missed injections, overdose, and risk of blood-borne disease transmission. Increased vulnerability to HIV/HCV infection within the context of intimate relationships was represented in participant narratives. IDU identified a lack of services available for those who require assistance injecting, with notable mention of restricted use of Vancouver's supervised injection facility. Conclusions This study documents numerous severe harms that arise from assisted injecting. Social structural factors that shape the risks related to assisted injection in the Vancouver context included intimate partner relations and social conventions requiring an exchange of goods for provision of injecting assistance. Health services for IDU who need help injecting should include targeted interventions, and supervised injection facilities should attempt to accommodate individuals who require assistance with injecting.